Mergers facing the tax reform for the year 2014 - Faúndez Ugalde, Antonio (Revista de Estudios Tributarios, 2016)
This article presents a study with the effects of taxation derived from corporate mergers’ processes, to be addressed in three periods: prior to the tax reform introduced by the Law 20.780, during the transition regulations emerging from the same Law No 20.780, to conclude with permanent norms from January 1st 2017